Rekonstruksi Makna Hidup pada Lansia dengan Riwayat Penolakan Keluarga - Fury Shafa Hartono; Nur Azizah (Scidacplus, 2026)
This study aims to examine the process of reconstructing the meaning of life among elderly individuals with a history of family rejection at the Panti Pelayanan Sosial Dewanata Cilacap. This research employed a qualitative approach with a phenomenological method to understand the subjective experiences of the elderly after experiencing family rejection. The informants consisted of three elderly residents and one social worker. Data were collected through in-depth interviews, observation, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing, with source triangulation used to ensure data validity. The findings revealed that family rejection, including emotional neglect, family conflict, verbal abuse, and lack of attention, caused psychological impacts such as sadness, loneliness, anxiety, insecurity, and a crisis in the meaning of life. Initially, the elderly experienced difficulties adapting to life in the nursing home and tended to withdraw socially. However, over time, they gradually reconstructed the meaning of life through self-acceptance, social support, social worker assistance, social activities, and spirituality. Spirituality became the most dominant factor in helping the elderly achieve inner peace, gratitude, and acceptance of their life experiences.